(Television) Quiz Show as a Way to a Successful Polish Language Lesson for Foreigners - Nowicka, Monika (Ludicity in (Glotto)Didactic, 2020)
The use of games in the glottodidactic process is becoming increasingly popular. Their positive influence on the learning outcomes is indisputable. Among them we can single out a quiz show, which should be more appreciated by teachers. The article presents its value and the specific possibilities of using it on Polish classes as a foreign language.